2016
DOI: 10.1209/0295-5075/114/64004
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric and plasma charging of microparticles

Abstract: The charge on two sets of 100 µm polystyrene particles has been measured using their acceleration in an externally applied electric field. This allows for the measurement of the individual charge on multiple particles at the same time. It is found that particles will charge each other both positive and negative due to the triboelectric effect. This leads to a broad particle-charge distribution with positive, negative and neutral particles. The particle charge can be largely removed by applying a plasma over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Moreover, it is concluded that there was no flow turbulence to the extent that it influenced the particle trajectories. Heijmans and Nijdam [28] have shown that the triboelectric charge of 100 μm polystyrene particles can be as large as ±5 × 10 6 e. This shows that the triboelectric particle charge can be of the same magnitude or even larger than the particle charge in the active plasma region.…”
Section: Sheath Above Mesh Gridmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, it is concluded that there was no flow turbulence to the extent that it influenced the particle trajectories. Heijmans and Nijdam [28] have shown that the triboelectric charge of 100 μm polystyrene particles can be as large as ±5 × 10 6 e. This shows that the triboelectric particle charge can be of the same magnitude or even larger than the particle charge in the active plasma region.…”
Section: Sheath Above Mesh Gridmentioning
confidence: 98%
“…First of all, it is virtually impossible to generate or directly inject neutral particles in a system because of the triboelectric effect [27]. Consequently, a charge control technique must be able to reset the triboelectrically induced charge distribution, which includes both positively and negatively charged particles [28].…”
Section: Introductionmentioning
confidence: 99%
“…The main element of the PPCI setup was a square glass tube filled with argon at 0.9 mbar (the base pressure was 5 × 10 −7 mbar). Monodisperse melamine formaldehyde (MF) particles were injected using a particle dispenser similar to those used in earlier studies 28,29 . These particles were (4.9 ± 0.2) µm in diameter and coated with a layer of silver of several hundred nanometers thickness to minimize triboelectric charging 30 .…”
mentioning
confidence: 99%
“…A determining part of this system was a 1 m long square glass tube. The operating pressure was 90 Pa argon, with a background pressure of 10 −9 Pa. At the top of the tube, particles were injected by a particle dispenser similar to the ones used in previous research 64 , 65 . In the dispenser’s container, the particles repeatedly collided with each other and with the container’s walls, thereby triboelectrically charging the particles 13 and aiding the natural conformation of clustered microparticles.…”
Section: Methodsmentioning
confidence: 99%